Triadism and Processuality - Juuso-Ville Gustafsson (University of Tartu Press, 2022)
In this short paper I examine the connection between triadism and processuality in peircean semiotics by comparing two reducibility thesis. I compare C.S. Peirce's irreducibility of triads and its corollary in semiotics, the triadic condition of the sign, with the irreducibility of processes. The comparison indicates that 1) there is a connections between the irreducibility of signs and the irreducibility of processes, 2) that the triadic condition of the sign entails process metaphysical commitments that in turn 3) urges us to reconsider the ontology of the sign from a process metaphysical perspective.